Comparison of Performance and Economic Efficiency for Greenhouse Solar versus Hot Air Drying: A Case of Crispy Mango Production - Kanokwan Kingphadung (2022)
This study aimed to compare the performance and economic efficiency of greenhouse solar and hot air drying. These are widely used and inexpensive techniques for preserved fruit production in Thailand. Two drying methods were used to dry mango fruit, var. Nam Dok Mai. During the process of both drying methods, the moisture content of mango slices was reduced from an average 85.6% to 12.5% wet basis. To determine the most profitable dryer system for investment, economic analyses of greenhouse solar and hot air drying, involving the main variables affecting their profitability, were investigated, including production and maintenance cost, capital costs, revenue, and drying capacities. The internal rate of return (IRR), net present value (NPV), benefit to cost ratio (BCR) and payback period (PBP) were all evaluated. The results of economic evaluation revealed that high values of IRR, NPV, and BCR, and low value of PBP made the two drying systems cost efficient. However, when the incremental rate of return (ROR) was determined, 66% incremental ROR was much greater than the minimum attractive rate of return (MARR = 4.875%). Consequently, the greenhouse solar drying method proved to be the most suitable method for small-to-medium-scale entrepreneurs to produce crispy mango.